Intellectual Capital's influence on the Financial Performance of Manufacturing Companies - R Rajindra (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to see the effect of intellectual capital on the financial performance of companies listed on the Indonesia Stock Exchange (BEI) in 2014-2016. This research is a quantitative research. This research was conducted at the Indonesia Stock Exchange through a representative of the Capital Market Information Center (PIPM), which is located at Jl. Dr. Sam Ratulangi No. 124, Makassar. Our research was conducted in two months, from March to April 2018. The population of this study were all manufacturing companies listed on the Indonesia Stock Exchange in the observation period from 2014 to 2016. While the sample of this research is a company selected from the population with purposive sampling criteria, namely as many as 10 companies. Sources of data in this study are secondary data. The data collection method used is the documentation method. The statistical method used to test the hypothesis is to use multiple regression with the help of SPSS for windows software. Our research results show that Human Capital Efficiency (HCE) has a positive and significant effect on Return On Assets, Structural Capital Efficiency (SCE) has a positive and insignificant effect on Return on Assets. And Capital Employed Efficiency (CEE) has a positive and significant effect on Return on Assets.